Ecological Predictors of the Parenting Behaviour of Malay Mothers - Baharudin, Rozumah (Universiti Putra Malaysia Press, 1996)
The primary purpose of this study was to identify factors related to the quality of the parenting behaviour of Malay mothers. The sample comprised 128 Malay mothers with children aged 8 to 9 years. The respondents were identified using a systematic sampling procedure. Data were collected by interviews and observation in the homes of the respondents. Parenting behaviour was assessed using the Home Observation for Measurement of the Environment (HOME) (Caldwell and Bradley 1984). Results of the study show that maternal characteristics, child characteristics, and contextual factors are all related to the parenting behaviour Malay mothers provide for their school-age children. Mothers with higher levels of education, selfesteem, and family income showed better quality parenting than other mothers in the study. However, mothers with a larger number of children, and those who perceive their children as difficult to care for demonstrated less supportive parenting behaviour. Findings from the study suggest that numerous factors within the ecology of the family may combine to influence the quality of care parents provide for their children. The findings, therefore, have important implications for planning parenting and family life education programmes.